Mobile Phones as a Source of Bacterial Infection - Najm, Najla; Garabulli, Fauzia (Scientific Journal for Faculty of Science-Sirte University, 2023)
Background: The wide spread of mobile phones in recent years inevitably raises the question of whether they are an exogenous source of infections. Design: A cross-sectional study was carried out among some teachers, educational staff, doctors, and nurses selected using the multi-stage stratified random sampling technique. 100 samples were collected from some teachers, educational staff, doctors, and nurses in some hospitals in Benghazi. Results: The organisms sequentially isolated in this study, based on colonial, morphological, and biochemical characteristics, were coagulase-negative Staphylococci (58%), Staphylococcus aureus (12%), Corynebacterium urealyticum (6%), Bacillus cereus (5%), Tatumella ptyseos (3%), Leuconostoc lactis, Pseudomonas aeruginosa, All isolates were resistant to more than one antibiotic. This revealed that mobile phones may have a notable role in the transmission of multidrug-resistant nosocomial pathogens. Conclusions: This study showed microbial contamination on personal mobile phones and hands. Some of the contaminated mobile phone microorganisms (such as Staphylococcus aureus) were epidemiologically important nosocomial drug-resistant pathogens. These isolates of bacteria were resistant to commonly used antimicrobials such as amoxicillin, gentamicin, and ciprofloxacin. These results showed that mobile phones and personal's hands were contaminated with various types of bacteria, which suggested that mobile phones (used by people in daily practice) may be a source of nosocomial infections.